L-Ornithine derivatives with structural hetaryl and alkyl moiety: Synthesis and antibacterial activity - T. G. Bodrova; U. A. Budanova; Yu. L. Sebyakin (Тонкие химические технологии)
Objectives. Cationic amphiphiles and antimicrobial peptidomimetics are widely investigated as antibacterial agents due to their membrane-active mechanism of action. Particular attention is focused on the rational design of compounds in this class to achieve high antimicrobial activity. The aim of the present work is to synthesize bivalent cationic amphiphiles with L-ornithine as a branching element and evaluate the effectiveness of their antibacterial action. The compounds differ in terms of hydrophobicity due to the variation of N-terminal aliphatic amino acids in the polar block and alternation of dialkyl and alkyl-hetaryl radicals in the lipophilic block.Methods. For the synthesis of nonpolar fragments of amphiphiles, methods for the alkylation of amines with alkyl bromides in the presence of carbonate salts were used. The formation of amide bonds of L-ornithine derivatives with amino acids was carried out using the carbodiimide method. For the reaction products recovery from the reaction mixture, column chromatography on silica gel and aluminum oxide activated Brockmann Grade II was used. The antimicrobial activity of the synthesized compounds against gram-positive B. subtilis 534 and gram-negative E. coli M17 bacterial strains was evaluated. Minimum inhibitory concentration (MIC) values were recorded using a serial microdilution method in a nutrient medium.Results. Developed schemes for the preparation of bivalent cationic amphiphiles based on L-ornithine derivatives are presented. Differences in the structure of aliphatic amino acids (glycine, β-alanine, γ-aminobutyric acid (GABA)), in the length of alkyl radicals (C8, C12), or in the presence of an indole moiety, were used in the design of target compounds. The high antibacterial activity of the synthesized compounds was demonstrated. The most active compounds were lipoamino acids with terminal GABA residues and asymmetrical non-polar block (tryptamyl–dodecylamine). The MIC values were 0.39 μg/mL for gram-positive bacteria and 1.56 μg/mL for gram-negative bacteria. A GABA derivative with a symmetrical lipophilic moiety based on dioctylamine demonstrated activity with an MIC of 0.78 μg/mL against B. subtilis and 3.12 μg/mL against E. coli.Conclusions. Nine new lipoamino acid cationic bivalent amphiphiles based on L-ornithine were synthesized. The structure of the obtained compounds was confirmed by nuclear magnetic resonance 1H spectroscopy and mass spectrometry data. Leading compounds in antimicrobial activity against both gram-positive and gram-negative strains of bacteria were determined. The influence of the degree of lipophilicity in the asymmetric nonpolar block on the level of exhibited antimicrobial activity is demonstrated.